Novel network virtualization architecture based on the convergence of computing,storage and transport resources - Bo LEI; Jianglong WANG; Qianying ZHAO; Yongzhi YU; Mingchuan YANG (Dianxin kexue)
With the development of 5G and edge computing,the multi-level and distributed deployment of basic IT resources such as computing resources and storage resources becomes mainstream.The way to provide users with more convenient and customized services to improve resource utilization becomes a new interest in network.The characteristics and development of the network virtualization,interworking trend and development of various resources,as well as the new requirements of emerging services for resource supply were analyzed.On the basis of the analysis,a network virtualization architecture based on multi-dimensional resource interworking was proposed.That is,multi-party and heterogeneous resources were integrated into a unified resource plane by introducing the process of resource discovery and resource transaction,and then resource slicing and virtualization were performed according to user requirements to meet the flexible resource requirements of emerging services.Resource utilization efficiency was improved effectively and operating cost was reduced.Since the joint optimization of resources involves multiple research fields,the network virtualization architecture will be constantly improved with the development of user requirements and business models,playing an important role for future services.